The morphological process of slang words used by teenagers in Jakarta and its negative effects in their academic qualifications (A sociolinguistic study) - Gunawan Tambunsaribu (English, 2019)
The use of slang words in teenagers’ life is common in every country in the world. But in every country, each language is different in its words’ formation. The sources, as well as the formations of such words, are different from each country. The objectives of this study are 1) to find out the lists of slang words including abusive words used by Jakartan’s teenagers; 2) to analyze the morphological features of such slang words, and 3) to find out the negative impacts of using such slang words based on parents as well as school teachers’ opinions. This study uses a qualitative approach. The collected data in this research will be analyzed and reported descriptively. The data are encrypted from the audio-recorders, questionnaires, and also taken from the interview session. The conclusion of this research is that there are ten word-formations of slang words used by Jakarta's teenagers in their speaking with others daily. The researcher found out 558 slang words which are usually used by Jakartan’s teenagers in their daily speaking with their peers. The 558 words are grouped into 10 word-formation; they are reduplication (0.4%), clipping (3.9 %), onomatopoeia (4.5%), borrowing (4.8 %), other formation - backward letters and backward syllables (5.9 %), inflection (8.1 %), acronym (11.8 %), mixed/multiple processes (12.2 %), coinage (17.4 %), and blending (31 %). Out of 150 respondents – 100 school-teachers and 50 lecturers – there are 129 respondents (86%) who stated that there are negative impacts of using slang words by the students in their academic qualification in the learning process in the class they are teaching. This research is expected to be useful for all people around the world especially for the knowledge of linguists, lecturers, teachers as well as parents in order to know and understand the meaning of slang words used by teenagers in their speaking with their peers in their communication with others daily.